Impact of Postoperative Venous Thromboembolism on Postoperative Morbidity, Mortality, and Resource Utilization after Hepatectomy. Issue 12 (December 2015) - Newhook, Timothy E.; Lapar, Damien J.; Walters, Dustin M.; Gupta, Shruti; Jolissaint, Joshua S.; Adams, Reid B.; Brayman, Kenneth L.; Zaydfudim, Victor M.; Bauer, Todd W.
The impact of venous thromboembolism (VTE) after hepatectomy on patient morbidity, mortality, and resource usage remains poorly defined. Better understanding of thromboembolic complications is needed to improve perioperative management and overall outcomes. About 3973 patients underwent hepatectomy within NSQIP between 2005 and 2008. Patient characteristics, operative features, and postoperative correlates of VTE were compared with identify risk factors for VTE and to assess its overall impact on postoperative outcomes. Overall incidence of postoperative VTE was 2.4 per cent. Risk factors for postoperative VTE included older age, male gender, compromised functional status, degree of intraoperative blood transfusion, preoperative albumin level (all P < 0.05), and extent of hepatectomy ( P = 0.004). Importantly, major postoperative complications, including acute renal failure, pneumonia, sepsis, septic shock, reintubation, prolonged ventilation, cardiac arrest, and reoperation were all associated with higher rates of VTE (all P < 0.05). Operative mortality was increased among patients with VTE (6.5% vs 2.4%, P = 0.03), and patients with VTE had a 2-fold increase in hospital length of stay (12.0 vs 6.0 days, P < 0.001). Postoperative VTE remains a significant source of morbidity, mortality, and increased resource usage after hepatectomy in the United States. Routine aggressive VTE prophylaxis measures are imperative to avoid development of VTE among patients requiring hepatectomy.